A Systematic Literature Review The Effect of Modification on Adsorption Performance of Banana Fiber (Musa Sapientum) in Treating Wastewater: A Systematic Review - Rosli, Nur Farah Aina binti; Jalil, Mas Rahayu binti (Progress in Engineering Application and Technology, 2022)
The utilization of banana fiber as biosorbent was expanded as a feedstock in wastewater treatment. The modification of banana fiber as biosorbent for efficient biosorption has gained interests among researchers. Therefore, in this study, the effect of modification of banana fiber as biosorbent in treating wastewater were analysed in terms of qualitative analysis via systematic review. Twenty-two (22) studies related to the effect of modification on banana fiber as biosorbent were identified via PRISMA method. Based on the findings, chemical modification on banana fiber has improved the surface area and biosorption capacity which resulted to the higher percentage removal of color and metal ions. The study also found that the effect of chemical modification can improve the stability of the banana fiber as biosorbent by applying wide range of pH from 1 to 12 resulted on higher percentage of removal of color and cationic metal. The effective range of pH which physically stable was in the range of 2 to 10. The removal efficiency of modified banana fiber can increase the proportion of active sites present on the surface of adsorbent and improved the ability of banana fiber in absorbing color and toxic metal ion at low dosage at range 0.1 to 0.5 g for removal up to 90%. Overall, the findings obtained provide comprehensive information and act as reference on improving the biosorption performance at wide range of working pH and lower sorbent dosage for further research on banana fiber as biosorbent.